CONTENTS OF THE EXPERIMENTAL PROFESSIONAL SPEECH TRAINING TARGETED FOR THE FUTURE TRANSLATORS OF CHINESE - Oleksandra Popova (Kherson State University, 2016)
The modern context of the Ukraine-China relations presupposes high requirements to a specialist-sinologist. A rapid development of the world's areas of science and technics alongside with corresponding transformation of the Chinese translator's professional framework stipulate the problem of curricula contents adaptation of normative and elective disciplines comprising the speciality "Philology. Translation (the Chinese language)", those ones of work training, professiogramma based on competencies, which causes some discord with traditional training methods of the future specialists in the aforementioned field. Therefore, the aim of the pedagogical research is to describe one of the up-to-date experimental professional speech training targeted for the future translators of the Chinese language within modern educational conditions. A great attention is paid to the role of information and communications technologies in the initiated training. Thus in the course of the experiment there were determined the stages of the experimental training; they are: cognitive-enriching, operational-reproductive, creative-productive and evaluative-reflexive stages. The integral training methods (systems of exercises, forms and methods of education; profession-targeted events; their correlation with pedagogical conditions of education, etc.) intended for the future translators-orientalists within the modern context of professional activity were specified. It should be mentioned that all the pedagogical conditions were implemented in an integrative way at each stage of the experimental training, which facilitated formation of the future translators-orientalists' competencies (linguistic, communicative / speaking, translation-discursive, linguosociocultiral, specific-technological) - a set of profession-targeted knowledge and skills, these competencies being components of the students' integral translation competence which was obtained by the students. Perspectives of the research are seen in the further advancement of training methods intended for the future translators-polylingues in the field of the state and foreign languages, in simultaneous translation in particular